Gene silencing and sex determination by programmed DNA elimination in parasitic nematodes. (August 2016) - Streit, Adrian; Wang, Jianbin; Kang, Yuanyuan; Davis, Richard E
Highlights: DNA elimination likely evolved independently in at least two groups of nematodes. Elimination process is precise, highly regulated, and conserved in ascarid nematodes. Ascarids eliminate repeats and ∼700 single copy genes to form the somatic genome. Ascarid CENP-A chromosome deposition defines DNA sequences for retention or elimination. Strongyloides removes one copy of the sex chromosome in males for sex determination. Abstract : Maintenance of genome integrity is essential. However, programmed DNA elimination removes specific DNA sequences from the genome during development. DNA elimination occurs in unicellular ciliates and diverse metazoa ranging from nematodes to vertebrates. Two distinct groups of nematodes use DNA elimination to silence germline-expressed genes in the soma (ascarids) or for sex determination ( Strongyloides spp.). Data suggest that DNA elimination likely evolved independently in these nematodes. Recent studies indicate that differential CENP-A deposition within chromosomes defines which sequences are retained and lost during Ascaris DNA elimination. Additional studies are needed to determine the distribution, functions, and mechanisms of DNA elimination in nematodes.